Effects of dietary zinc source and level on nursery pig performance - Jordan, K. E.; Gourley, K. M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S.; DeRouchey, Joel M.; Woodworth, Jason C.; Usry, J. L. (My University, 2016)
A total of 360 pigs (initially 5.9 ± 0.14 kg BW) were used in a 28-d study to evaluate the effects of dietary Zn source and level on weanling pig growth performance. Pigs were randomly allotted to pen at weaning by initial BW. The pen was assigned in a completely randomized design to 1 of 9 dietary treatments arranged in a 2 × 4 + 1 factorial. There were 8 pens per treatment and 5 pigs per pen. The corn-soybean meal based diets consisted of a control diet containing 110 ppm Zn from ZnSO4 from the trace mineral premix or the control diet with 390, 890, 1890, or 2890 ppm added Zn from either tetrabasic Zn chloride (TBZC; Intellibond Z; Micronutrients, Indianapolis, IN) or ZnO. This provided diets with a total of 500, 1000, 2000, or 3000 ppm added Zn. A 3 phase diet series was used with treatment diets fed during Phase 1 (d 0 to 7), Phase 2 (d 7 to 21) and Phase 3 (d 21 to 28). There were no Zn source × level interactions or Zn source differences observed for growth performance. From d 0 to 21, increasing Zn increased (linear; P ? 0.05) ADG and ADFI with no difference in G:F. From d 21 to 28, pigs fed increasing Zn had increased (linear; P = 0.018) ADFI resulting in decreased G:F (quadratic; P = 0.041). Overall, from d 0 to 28, increasing Zn increased (linear; P ? 0.05) ADG and ADFI without influencing G:F. On d 28, fecal samples were collected from 3 pigs in each pen and analyzed for DM content. There was a tendency (P = 0.081) for a Zn source × level interaction as increasing Zn from TBZC decreased fecal DM, whereas no difference in fecal DM was observed for increasing Zn from ZnO. In conclusion, increasing dietary Zn up to 3000 ppm increased ADG and ADFI but no differences existed between sources evaluated.
Citation: Jordan, K. E., Gourley, K. M., Tokach, M. D., Goodband, R. D., Dritz, S. S., DeRouchey, J. M., . . . Usry, J. L. (2016). Effects of dietary zinc source and level on nursery pig performance. Journal of Animal Science, 94, 139-139. doi:10.2527/msasas2016-297
Keywords: Growth Performance; Nursery Pig; Zinc; Agriculture